Effect of quercus infectoria extracts on dermal wound healing in rats and assessment of its antimicrobial activity / Syed Iklls Sayed Mohamad - Sayed Mohamad, Syed Iklls (2006)

(untitled)
In this study, Quercus infectoria (Manjakani) was test for its effectiveness in accelerating wound healing process and assessment on its antimicrobial activity. This study comprises of animal study (wound healing) and antimicrobial study. 4' groups of Sprague Dawley rats consists of 6 rats in each group were used in animal study. Ethanol and aqueous extracts of the plant were used. The rate of healing, rate of infection and histological structure of each group was assessed to observe the effect of each treatment. The result of the wound healing study show that that Solcoseryl® jelly (positive control) treated mouse healed in 11 days whereas the rats treated with Vaseline™ Petroleum jelly (negative control) taking about 13 days to healed. The rats treated with aqueous extracts of Q. infectoria healed in 12 days and rats treated with ethanol extracts healed within 12 to 13 days. Solcoseryl® jelly (positive control) accelerates healing faster than the other, followed by aqueous extracts, ethanol extracts and finally Vaseline™ Petroleum jelly. No infection was found and wounds treated with Solcoseryl® jelly and Q. infectoria (ethanol and aqueous) extract showed good histological structure. Only Coagulase negative Staphylococci were identified on the wound site. From antimicrobial study, Spot Lawn test showed 10% wlw ethanol and aqueous extracts of Q. infectoria gave significant zone of inhibition on S. aureus and E. coli. The effects of antibacterial study are more potent on Gram positive bacteria (S. aureus). Compound test showed that Q. infectoria extracts contain Polyphenol and Tannin constituents. The result from animal study proved that Q. infectoria having beneficial effect on wound healing Abstracts compared to negative control. Wound healing properties of Q. infectoria probably due to its phytochemical compounds. However, further study needs to be carried out to identify the compounds and assess the mechanisms responsible for both properties.